(untitled) (Prosiding Keislaman dan Sains, 2025)
This article aims to determine the improvement of children’s socialization skills at Flamboyan Kindergarten, Pagaruyung Village, Tapung District, Kampar Regency. The purpose of the outbound method is to develop an attitude of openness and courage while enjoying nature among each individual. Therefore, the experience of participating in outbound activities will provide children with lessons to understand teamwork as one of the keys to mutual success. The outbound method has not been fully implemented at the school, the implementation of outbound at the school has been carried out but has not been maximized, the school holds outbound activities at the end of each theme peak, where in the implementation of this outbound the school aims to improve children’s socialization skills and avoid learning boredom for students. The outbound method is applied in improving children’s socialization skills at Flamboyan Kindergarten. This type of research is classroom action research (CAR). The subjects used in this study were 13 Flamboyan Kindergarten children. The subjects used in this study were 13 Flamboyan Kindergarten children. The data for this classroom action research was collected through the observation method using an observation sheet. Data analysis used descriptive statistical analysis. This research was conducted in two cycles, namely Cycle I and Cycle II, which consist of the planning stage, implementation stage, observation stage, and reflection stage. The results of the study obtained in the pre-action showed that the average percentage of children’s socialization skills were in the criteria of not yet developed, which was 77%, after that the action was carried out in Cycle I, there was an increase in socialization skills starting to develop by 69%. However, in Cycle I, the results had not yet reached the success criteria so that action was carried out in Cycle II and experienced an increase in the average percentage of development according to expectations to 15.383%, and very well developed 84.62%. This shows that there is an increase in children’s socialization skills at Flamboyan Kindergarten from Cycle I to Cycle II. So the application of the outbound method can improve children’s socialization skills at Flamboyan Kindergarten. Keywords: Outbound Method, Socialization Skills, Early Childhood.